2012
DOI: 10.1111/1471-0307.12015
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of zinc oxide nanoparticle suspensions on food‐borne pathogens

Abstract: Nanoparticles (NPs) are increasingly recognised for their utility in biological applications including nanomedicine and food safety. The present study investigated the antibacterial activity of zinc oxide (ZnO) when tested against the Gram-negative bacteria Escherichia coli as well as the Gram-positive bacterium Staphylococcus aureus, and the effect was more pronounced with the Gram-positive than with the Gram-negative bacteria. ZnO NPs also exhibited a preferential ability to suppress growth of E. coli and S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 21 publications
4
47
0
Order By: Relevance
“…ZnO quantum dots used as antimicrobial agents significantly inhibited L. monocyto genes and Salmonella Enteritidis in liquid egg whites (18). Similar inhibitory effects of ZnO NPs on S. aureus and E. coli have been observed in milk samples (27). Juneja and Eblen (20) , no greenish discoloration and putrid odor: + , greenish discoloration and putrid odor.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…ZnO quantum dots used as antimicrobial agents significantly inhibited L. monocyto genes and Salmonella Enteritidis in liquid egg whites (18). Similar inhibitory effects of ZnO NPs on S. aureus and E. coli have been observed in milk samples (27). Juneja and Eblen (20) , no greenish discoloration and putrid odor: + , greenish discoloration and putrid odor.…”
Section: Discussionsupporting
confidence: 55%
“…These elements have been used for food preservation (18,27) and to decontaminate surfaces in industrial environments. These elements also have been used in active food packaging for such properties as ethylene oxidation or oxygen scavenging, which can extend food shelf life (24).…”
mentioning
confidence: 99%
“…This study suggested that the application of ZnO NPs as antibacterial agent in food systems and medicine may be effective at inhibiting certain pathogens. Also the same result, carried out to reduce E. coli and S. aureus in milk samples [32].…”
Section: 2mic and Mbc Testsmentioning
confidence: 91%
“…Moreover, ZnO nanoparticles present high antimicrobial activity against a range of bacteria strains, in particular S. aureus (Li et al 2008). Mirhosseini and Firouzabadi (2012) investigated ZnO antibacterial activity against E. coli and S. aureus. As aforementioned, ZnO nanoparticles were more effective toward S. aureus strain, showing inhibition zones of 10 and 12 mm at the concentrations of 5 and 10 mM, respectively.…”
Section: Nanomaterials: Antimicrobial Properties and Mechanisms Of Acmentioning
confidence: 99%